Term alpaca placenta glycosylation profile and its correlation with pregnancy maintenance and fetal survival - Navarrete Zamora, Miluska Beatriz; Silva, Thamires Santos da; Silva, Mônica Duarte da; Almeida, Gustavo Henrique Doná Rodrigues; Silva-Júnior, Leandro Norberto da; Horvath-Pereira, Bianca de Oliveira; Baracho Hill, Amanda Trindade; Acuña, Francisco; Carreira, Ana Claudia Oliveira; Barreto, Rodrigo da Silva Nunes; Sato, Alberto Sato; Miglino, Maria Angélica (Frontiers in Cell and Developmental Biology, 2023)
Alpaca is a South American camelid, particularly present in Peruvian highlands, where oxygen concentration and atmospheric pressure are very low. Due to this fact, gestational physiology has adapted to preserve the conceptus’ and mother’s health. In this context, several cellular and molecular features play an essential role during and at the end of gestation. Structural carbohydrates act on maternal–fetal communication, recognize exogenous molecules, and contribute to placental barrier selectivity. Therefore, this study aimed to characterize the structural carbohydrate profiles that are present in the term alpaca placenta, kept in their natural habitat of around 4,000 m height. For this propose, 12 term alpaca placentas were collected, and the material was obtained at the time of birth from camelids raised naturally in the Peruvian highlands, in the Cusco region. All placenta samples were processed for histological analysis. A lectin histochemical investigation was performed using 13 biotinylated lectins, allowing us to determine the location of carbohydrates and their intensity on a semi-quantitative scale. Our results demonstrated that during term gestation, the epitheliochorial alpaca placenta shows a high presence of carbohydrates, particularly glucose, α-linked mannose, N-acetylglucosamine β (GlcNAc), galactose (αGal), and N-acetylgalactosamine α (GalNAc), present in the trophoblast, amnion epithelium, and mesenchyme, as well as the presence of sialic acid residues and low affinity for fucose. In fetal blood capillaries, the presence of bi- and tri-antennary complex structures and α-linked mannose was predominated. In conclusion, we characterized the glycosylation profile in the term alpaca placenta. Based on our data, compared to those reported in the bibliography, we suggest that these carbohydrates could participate in the labor of these animals that survive in Peruvian extreme environments.